Chemistry of the Climate System. Volume 1, - Möller, Detlev (De Gruyter, 2019)
Climate change is a major challenge facing modern society. The chemistry of air and its influence on the climate system forms the main focus of this book. Vol. 1 of Chemistry of the Climate System provides the reader with a physicochemical understanding of atmospheric processes. The chemical substances and reactions found in the Earth's atmosphere are presented along with their influence on the global climate system.- Resumé vydavatel
Volume 2 of 3rd edition not yet published (July 17, 2020).
Keywords: atmosféra; chemie atmosféry; klimatické změny; meteorologie; atmosphere; atmospheric chemistry; climate changes; meteorology; elektronické knihy; monografie; electronic books; monographs